Editorial - Mackinlay, Elizabeth; Nakata, Martin (The Australian Journal of Indigenous Education, 2014)
We are very proud to present this timely and significant Special Issue of The Australian Journal of Indigenous Education, guest edited by Katelyn Barney (The University of Queensland), Cindy Shannon (The University of Queensland) and Martin Nakata (The University of New South Wales). This collection of articles focuses on the activities of the Australian Indigenous Studies Learning and Teaching Network, an initiative funded by the Office for Teaching and Learning. The Australian Indigenous Studies Learning and Teaching Network was formed to bring leaders and early career academics in the field together to build relationships, debate and discuss central issues, and explore and share teaching and learning strategies in the discipline at tertiary level. These discussions at once untangle and re-entangle the processes, pedagogies and politics at play when Indigenous Studies becomes defined as a discipline.